A novel prenyl-polybasic domain code determines lipid-binding specificity of the K-Ras membrane anchor. (3rd May 2020) - Zhou, Yong; Hancock, John F.
ABSTRACT: Ras proteins must localize to the plasma membrane (PM) for biological function. The membrane anchor of the K-Ras4B isoform comprises a farnesylated and methylated C-terminal cysteine together with an adjacent hexa-lysine polybasic domain (PBD). Traditionally, polybasic sequences have been thought to interact electrostatically with negatively charged membranes showing no specificity for anionic lipid head groups. By contrast we recently showed that the K-Ras membrane anchor actually exhibits a very high degree of specificity for phosphatidylserine (PtdSer). The selectivity for PtdSer is determined by a combinatorial code comprising the PBD sequence plus the prenyl anchor. Lipid binding specificity is therefore altered by PBD point mutations that in turn modulate signaling output. For example, mutating Lys177 or Lys178 to glutamine switches K-Ras4B lipid affinity from PtdSer to phosphoinositol 4, 5-bisphosphate (PIP2 ). Changing the lipid anchor from farnesyl to geranylgeranyl or the PBD lysines to arginines also changes lipid binding specificity. All-atom molecular dynamics simulations reveal the structural basis for these K-Ras anchor lipid-binding preferences. Here we examine the PM interactions of a series of geranylgeranylated PBD mutants and provide further evidence that the precise PBD sequence and prenyl lipid determines lipid sorting specificity of the K-Ras anchor and hence biological function.